Covid-19 and cacophony of coughing: Did international commodity prices catch influenza? - Hillary Chijindu Ezeaku; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
The Covid-19 outbreak has led to extensive declines in international commodity prices. The outbreak as well as measures fashioned to contain it has been weighing down on global supply chains and commodity prices. The pandemic has been accompanied with unprecedented shock that has disrupted both the demand and supply of commodities. In view of the widespread global impact of Covid-19, this paper analyses the impact of the outbreak on global commodity prices with particular emphasis on the energy, agricultural and metals and materials sectors using international global prices and indices to trend the movements. In the wake of oil price war and dampened oil demand, the energy sector was the most hit with 15% average monthly decline in energy indices between December 2019 and April 2020. Oil recorded its largest one-month plunge on record in March. Movements in coal indices showed more resilience to the pandemic compared to crude oil and natural gas. Base metals were the most affected sector after energy with -3.49% average monthly changes in indices between December 2019 and April 2020. Of the major base metals and minerals, aluminum appears less affected by the outbreak compared to copper and zinc. In contrast, precious metals prices and indices remain stable and is the only commodity sector with positive monthly average change (1.99%) during the period. Gold prices maintained steady gains while silver and platinum prices followed a similar but weaker trend. The agricultural commodity indices largely maintained strong upward movement but plummeted at monthly average of 0.89% between December 2019 and April 2020. Grains and cereals proved more resilient to Covid-19 pandemic compared to timber, beverages, raw materials, and oils & meals.
Keywords: H12; I12; O10; 330; Covid-9; Commodity Prices